PALESTINIAN-ISRAELI CONFLICT IN WAR AND PEACE APPROACH - Marlini Alianita; Eva Achjani Zulfa; Bayquni (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
The Palestinian-Israeli conflict is a conflict that has been going on for decades and has not been resolved even though it has involved many countries to encourage the implementation of the peace process. The Palestinian-Israeli conflict is multifaceted, with various internal and external factors influencing the course of the conflict. In this paper the author tries to examine what approaches have been used in resolving the conflict, the method used by the author in compiling this paper is a qualitative descriptive approach based on literature studies or library research. In this paper the author finds that various initiatives and peace negotiations have been attempted to end the conflict between Palestine and Israel, ranging from the Reconciliation approach, the approach to the formation of two states to the proposal of confederation have also been carried out, but this has not found enlightenment in its settlement thus making it difficult for leaders to find common ground. Internationally, regional power dynamics, national interests, and external interventions are increasingly complicating the path to peace and to date the two-state solution remains the most widely supported option, the greatest challenge of which lies in addressing core issues and reconciling competing national aspirations. Achieving peace and stability in the region requires sustained dialogue, compromise, and commitment from all stakeholders involved.